2020
DOI: 10.1186/s40359-020-0388-7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between existential well-being and mood-related psychiatric burden in Indian young adults with attachment deficits: a cross-cultural validation study

Abstract: Background: Attachment and spirituality are thought to have deep evolutionary roots but are always interpreted within the framework of culture, religion and personal beliefs. While insecure attachment has been observed to be positively related with psychopathology, a positive mental health effect has often been described for spirituality. To examine the cross-cultural validation of previous research focused on Austrian young adults with Western socialization, we attempt to replicate our study examining the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…The more recent Multidimensional Inventory for Religious/Spiritual Well-being (MI-RSWB) also includes a EWB subscale (Unterrainer et al, 2010). Using these measures, higher EWB is associated with better mental health and wellbeing, higher self-esteem, and lower levels of depression (Genia, 2001;Hiebler-Ragger et al, 2020).…”
Section: How To Measure Existential Wellbeingmentioning
confidence: 99%
“…The more recent Multidimensional Inventory for Religious/Spiritual Well-being (MI-RSWB) also includes a EWB subscale (Unterrainer et al, 2010). Using these measures, higher EWB is associated with better mental health and wellbeing, higher self-esteem, and lower levels of depression (Genia, 2001;Hiebler-Ragger et al, 2020).…”
Section: How To Measure Existential Wellbeingmentioning
confidence: 99%
“…Two broad categories of studies were identified: those focused on somatization as an entity in its own right, as defined by the DSM diagnostic classifications, and those considering somatic complaints as part of a broader picture, such as depression (22)(23)(24)(25)(26)(27)(28)(29), or of a still broader entity comprising the so-called "internalizing symptoms, " which encompass anxiety, depression, and somatization (24, [30][31][32][33][34][35][36][37][38].…”
Section: Entanglement Between Anxiety and Depressionmentioning
confidence: 99%